Review of Inclusiveness of Selected Subhead Accounting Items with IPSASs Compliance in Sovereign Entities Consolidated Financial Statements - Christopher Enyioma Alozie (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2026)
Backgrounds: Sovereign countries that have issued national accounting standards based on IFRS and public sector accounting standards to meet requirements of domestic public financial laws, operating environments, and systems. But implementation is mainly drawn from IPSASs conceptual framework with the degree of similarity in public accounting systems varying across jurisdictions aimed at achieving full IPSASs compliance. Objectives:  The research reviews inclusiveness of relevant subhead accounting items and IPSASs compliance in government consolidated financial statements.     Methodology: Ex-post quantitative and quantitative methods are adopted, with datasets extracted from sovereign entities financial statements used in analysis. Fisher’s exact test analysis technique is applied as test statistic in deriving results. Findings: Results showed Treasury Single Account/Consolidated Revenue Fund, and fixed capital assets were satisfactorily reflected in consolidated financial statements. While the remaining four pairwise accounting head-items: official portion of national foreign reserves, sovereign wealth funds; heritage assets; and decentralisation of MDAs accounting were not given improper treatments and non-inclusive in consolidated financial statements. Conclusions: Without rectification of these accounting errors, omission, and non-inclusion of subhead accounting items, there are deficiencies in sovereigns audited financial statements. An interim solution, IPSASB/IFRS should also make professional pronouncements, authorising disclosure of SWF financial position as notes in government consolidated financial reporting pending issuance of formal standards.